The Sustainable Culture and Entrepreneurial Orientation as Antecedents of Socially Sustainable Supply Chain - Pattaravis Yoowattana; Boriboon Chalong; Kulnaree Maneechote (International Journal of Supply Chain Management, 2019)
This study contributes to the literature on SSCM through analyzing the influence of entrepreneurial orientation and culture on the implementation of social sustainable practices in supply chain. The previous research studies have focused on the external and structural forces or the purchasing function. The study has used the SEM-PLS for the analysis of data collected from the manufacturing SEMs operating in Thailand. The current research contributes to the existing literature through giving evidence of strategic choice and cultural attributes possessed by a firm. Moreover, it reflects that basic social practices in the supply chain are the result of sustainability culture. The impact of sustainability culture on the implementation of advanced social practices in supply chain is influenced through entrepreneurial orientation. This study has analyzed the decision-making orientation and internal culture of a firm and the combined influence on the selection of social sustainable practices in supply chain. It has been revealed through results that advance and basic social sustainable practices across the supply chain is positively linked with the level of sustainability culture of a firm. A strong positive association is shown between the sustainability culture of a firm and implementation of both types of social sustainable practices in supply chain. The relation between the adoption of sustainable practices and sustainability culture is variable effected by entrepreneurial orientation. There is no considerable affect entrepreneurial orientation on the basic practices and sustainability culture. This contradicts with the hypothesis that the relation between basic practices of social sustainability in the supply chain and sustainability culture is influenced through entrepreneurial orientation. The study will be helpful for policymakers and researchers.